Improving Appropriateness and Quality in Cardiovascular Imaging: A Review of the Evidence. (December 2015) - Bhattacharyya, Sanjeev; Lloyd, Guy
Abstract : High-quality cardiovascular imaging requires a structured process to ensure appropriate patient selection, accurate and reproducible data acquisition, and timely reporting which answers clinical questions and improves patient outcomes. Several guidelines provide frameworks to assess quality. This article reviews interventions to improve quality in cardiovascular imaging, including methods to reduce inappropriate testing, improve accuracy, reduce interobserver variability, and reduce diagnostic and reporting errors.